TEACHING ENGLISH VOCABULARY TO HEARING IMPAIRED STUDENTS:Qualitative Research on SLBN-B in Bandung - Rona Ardi Mustofa, - (2011)
This study aims at finding out what strategies used by the teacher to teach vocabulary and problems which arise to teach vocabulary to hearing impaired students. There were two instruments employed, namely; observation and Interview to describe learning strategies employed by the teacher in SLBN-B in Bandung. The findings show that the teacher used the same method and strategies in teaching vocabulary. They were questioning for comprehension checking (QCC), drilling, game, discussion, lecturing and total communication. The problems faced by the teacher in teaching hearing impaired students were time allocation, grammatical structure differences, sourcebooks and material delivery.